Lipid-based biomarkers for CVD, COPD, and aging – A translational perspective. (April 2020) - Ekroos, Kim; Lavrynenko, Oksana; Titz, Bjoern; Pater, Calin; Hoeng, Julia; Ivanov, Nikolai V.
Abstract: For many diseases, there is an unmet need for new or better biomarkers for improved disease risk assessment and monitoring, as available markers lack sufficient specificity. Lipids are drawing major interest as potential candidates for filling these gaps. This has recently been demonstrated by the identification of selective ceramides for prediction of cardiovascular mortality, enabling improved risk assessment of cardiovascular disease compared with conventional clinical markers. In this review, we discuss current lipid biomarker findings and the possible connection between cardiovascular disease, chronic obstructive pulmonary disease, and aging. Moreover, we discuss how to overcome the current roadblocks facing lipid biomarker research. We stress the need for improved quantification, standardization of methodologies, and establishment of initial reference values to allow for an efficient transfer path of research findings into the clinical landscape, and, ultimately, to put newly identified biomarkers into practical use.